Student Motivation in Thematic Learning at Elementary Schools - Mohamad Maulidin Alif Utama (Faculty of Education and Teacher Training of UINSI Samarinda, 2020)
The purpose this article is to describe learning motivation in the application of integrative thematic learning, relationship between the implementation of thematic learning and student motivation, and thematic learning in fostering learning motivation. As a reflection of the development of increasingly advanced educational technology, changes in learning from conventional learning approach to thematic learning implementation is an innovation process in learning as an improvement effort in improving education. Therefore, the implementation of thematic learning is an important aspect in the success of student learning, especially in improving students' learning arousal or student learning motivation. The method used is library research and the result is discussed descriptively. The application of thematic learning can foster student motivation. Students will pay more attention to the lesson. With the advantages of thematic learning, it is very suitable if thematic learning is a beacon in motivational growth, as thematic learning becomes the guidance in fostering student learning motivation.